2021
DOI: 10.1016/j.heliyon.2021.e07805
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional immunity: targeting fungal zinc homeostasis

Abstract: Transition metals, such as Zn 2þ , are essential dietary constituents of all biological life, including mammalian hosts and the pathogens that infect them. Therefore, to thrive and cause infection, pathogens must successfully assimilate these elements from the host milieu. Consequently, mammalian immunity has evolved to actively restrict and/or pool metals to toxic concentrations in an effort to attenuate microbial pathogenicity -a process termed nutritional immunity. Despite host-induced Zn 2þ nutritional imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…These samples also presented copper and zinc in their composition. Both elements are important enzymatic cofactors needed during fungal parasitism ( Culbertson et al, 2020 ; Alamir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These samples also presented copper and zinc in their composition. Both elements are important enzymatic cofactors needed during fungal parasitism ( Culbertson et al, 2020 ; Alamir et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Goliath cells are formed primarily under zinc starvation conditions what is related with immune system's strategy of limiting the development of infection [79,136]. Phylogenetic and phenotypic analyses showed that the cell enlargement as response to zinc starvation was species-specific and developed in the common ancestor of C. albicans, C. dubliniensis and C. tropicalis and was not observed in other Candida species studied so far [2,79]. It is well known that many other species of the genus Candida can form pseudohyphae, however these structures do not display the virulence characteristics known to true hyphae [119].…”
Section: Morphological Transformation As a Strategy To Averting The H...mentioning
confidence: 97%
“…Nutritional immunity primarily affects enzymatic and metabolic functions, while metal overload contributes to the generation of ROS, reactive nitrogen species, protein mismetallization, and subsequent respiratory arrest. 533 , 537 539 …”
Section: Role Of Cellular Zinc Metabolism Under Physiological Conditionsmentioning
confidence: 99%